2019
DOI: 10.26444/aaem/105142
|View full text |Cite
|
Sign up to set email alerts
|

Stress at intellectual work and cardiovascular diseases in women at non-mobility working age

Abstract: Introduction and objective. Stress at the work place reduces efficiency, as well as increasing accidents and absences, which may cause various diseases, including cardiovascular diseases. The aim of the study is an analysis of the prevalence and causes of stress in intellectual work, and its correlation with the prevalence of cardiovascular diseases in women at non-mobility working age. Materials and method. The study was conducted in 2016-2017 in a group of 300 women aged 45-60 in non-manual employment. A que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The relationship between psychological stress and mitochondrial parameters was evaluated in a sample consisted of 129 (47 physicians, 49 nurses, and 33 technicians), of whom 63% was female and 77% was a nonsmoker. All participants were in good health with normal respiratory and cardiac parameters (systolic and diastolic pressure = 122 [16] and 79 [9] mm Hg, respectively, and heart rate = 75 [19] beats/min). Of these 129 health care workers from which blood samples were collected, only 41 (32%) individuals returned valid health questionnaires.…”
Section: Characteristics Of Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between psychological stress and mitochondrial parameters was evaluated in a sample consisted of 129 (47 physicians, 49 nurses, and 33 technicians), of whom 63% was female and 77% was a nonsmoker. All participants were in good health with normal respiratory and cardiac parameters (systolic and diastolic pressure = 122 [16] and 79 [9] mm Hg, respectively, and heart rate = 75 [19] beats/min). Of these 129 health care workers from which blood samples were collected, only 41 (32%) individuals returned valid health questionnaires.…”
Section: Characteristics Of Participantsmentioning
confidence: 99%
“…In addition to (work-related) psychological distress, toxic agents in the work environments can also affect physiological functions (13)(14)(15). Occupational stress related to both psychological problems and toxic agents represent a main cause of stress-related problems in the workplace (16,17), and it has been reported that high levels of stress at the workplace reduce efficiency and negatively influence work-related performance (18).…”
Section: Introductionmentioning
confidence: 99%
“…The postmenopausal period in women may have a significant role in the occurrence of adaptive disorders leading to high levels of stress. A decrease in estrogen production results in its reduced protective activity in the circulatory system, which, in consequence, increases the risk of cardiovascular diseases [ 6 ].…”
Section: Introductionmentioning
confidence: 99%